과제연구 프로그램이 고등학생들의 과학 탐구능력 및 과학에 관련된 태도에 미치는 영향 - 정혜영; 문성배; Jung, Hae-Young; Moon, Seong-Bae (대한지구과학교육학회지, 2014)
The purpose of this study is to investigate the effects of research project program of science process skills and science-related attitudes for high school students. This study were accompanied by 72 junior students of G High School who were reorganized as students whose research subject was closely related to chemistry. These students went through 28 periods of 14 sessions of research project program, were tested before and after the study on their science process skills and science-related attitudes. A simple questionnaire afterwards to get their thoughts on this program, was surveyed. The results are as follows. First, the research project program was effective in the science process skills (p<0.01). There was a statistically meaningful difference in the subcategory of deduction, setting up hypotheses, finding variables, building experiments, graphing and interpreting data. Although there was an increase in the average scores of prediction, operant definition, and generalization factors, it was not statistically meaningful (p>0.05). Second, the research project program showed an increase in the post-test of the science-related attitudes but was not statistically meaningful (p>0.05). In terms of subcategoty, the social importance of science, criterion of scientists, application of scientific attitude, and enjoyment of science classes were statistically meaningful (p<0.05). Third, according to the survey of research project program, there was an increase in creating a research problem and solving it by oneself as well as in participating with other teammates to solve a problem. But the most difficult thing was when the experiment failed during the research was processing. The curiosity and interest, towards objects around all lives and science classes after the program done, were increased.